Extrinsic magnetism in Co-doped BaTiO3 powders prepared by sol-gel route. Issue 16 (December 2016) - Lemziouka, H.; Moubah, R.; Rachid, F.Z.; Jouane, Y.; Hlil, E.K.; Abid, M.; Lassri, H.
Abstract: We report on the structural, magnetic, and magnetocaloric properties of Ba1−x Cox TiO3 (x=0, 0.02, and 0.03) powders prepared by sol-gel technique. X-ray diffraction shows that pure BaTiO3 powders crystallize in a tetragonal phase with a transition to pseudo-cubic phase after Co doping. Using the modified Brillouin modelling of the isothermal magnetization at various temperatures, we report that the magnetism of our system is extrinsic and due to the existence of antiferromagnetic cobalt oxide particles randomly distributed, which are undetectable by structural analyses. We discuss the existence of particles by the low enthalpy formation of cobalt oxides (high stability). Furthermore, it is demonstrated that the Ba0.97 Co0.03 TiO3 sample exhibits a magnetocaloric effect with a maximum magnetic entropy change of 50 mJ/kg K for a magnetic field change of ΔH=50 kOe at 3 K.